BUSINESS COMPETITION FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Yulitasari, Lis; Suharto, Suharto (STMIK Pringsewu, 2023)
This article discusses the concept of business competition from an Islamic economic perspective. Islam regulates how to get sustenance in a good, lawful, and clean way. One form of seeking sustenance is by doing business. Ethics in business is a knowledge of procedures for managing a business that pays attention to the norms. One of the things regulated in Islam is ethics in business competition. The competition itself has meaning when organizations or individuals compete to achieve the goals desired by consumers, market share, survey rankings, or the resources needed. When Islam allows business and encourages the wheels of the economy to run, Islam allows the implementation of business competition as long as it is within the corridors of fairness and by Islamic law.